Enhanced properties for visible-light-driven photocatalysis of Ag nanoparticle modified Bi2MoO6 nanoplates - Anukorn Phuruangrat (2018)
© 2015 Elsevier Ltd. All rights reserved. The visible light driven Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > photocatalyst doped with different contents of Ag nanoparticles was successfully synthesized by a combination of hydrothermal and sonochemical methods. The as-synthesized samples were characterized by X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning and transmission electron microscopy (SEM and TEM) and UV-visible spectroscopy to investigate crystalline structure, morphology, composition and photocatalytic properties. XRD patterns and TEM images of the samples revealed pure phase orthorhombic Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > nanoplates without any detection of Ag dopant due to its low concentration and very tiny particle size. TEM images showed that Ag nanoparticles with the size of 10-15 nm were dispersed randomly on the surface of Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > . The XPS analysis of Ag/Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > nanocomposites revealed the presence of additional metallic Ag. Photocatalytic activities of the Ag/Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > nanocomposites were evaluated by determining the degradation of rhodamine B (RhB) under visible light radiation. In this research, the 10 wt% Ag/Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > nanocomposites showed the best photocatalytic activity. The results suggest that the dispersion of Ag nanoparticles on the surface of Bi < inf > 2 < /inf > MoO < inf > 6 < /inf > significantly enhances its photocatalytic activity.